2016
DOI: 10.3390/fi8040048
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Semantic-Based Context-Aware Platform for Mobile Applications in Pervasive Environments

Abstract: Currently, the field of smart-* (home, city, health, tourism, etc.) is naturally heterogeneous and multimedia oriented. In such a domain, there is an increasing usage of heterogeneous mobile devices, as well as captors transmitting data (IoT). They are highly connected and can be used for many different services, such as to monitor, to analyze and to display information to users. In this context, data management and adaptation in real time are becoming a challenging task. More precisely, at one time, it is nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…This research work also demonstrated that ontology-based methods provide better solutions for the heterogeneity problem and that high-security and privacy can be ensured within smart homes. In [53], researchers developed a context platform, Kali-Smart, by incorporating an ontology to collect contextual information from sensors for adapting system behavior and semantic event detection and to provide services to clients in a ubiquitous environment. Recently in [42], a knowledge-based modeling of a UAV recorded video scenario was introduced.…”
Section: B Ontologies In Video Surveillancementioning
confidence: 99%
“…This research work also demonstrated that ontology-based methods provide better solutions for the heterogeneity problem and that high-security and privacy can be ensured within smart homes. In [53], researchers developed a context platform, Kali-Smart, by incorporating an ontology to collect contextual information from sensors for adapting system behavior and semantic event detection and to provide services to clients in a ubiquitous environment. Recently in [42], a knowledge-based modeling of a UAV recorded video scenario was introduced.…”
Section: B Ontologies In Video Surveillancementioning
confidence: 99%
“…Semantic Web technologies are currently bound to a request-response interaction paradigm. An effort toward a publish/subscribe enhanced version of Semantic Web technologies has been made by several researchers, like Murth et al [25], Alti et al [26] and Schade et al [27]. Adapting Semantic Web technologies to more dynamic scenarios is a task carried on also by the Smart-M3 community, which proposes a broker-centric publish/subscribe architecture pivoting the SPARQL language.…”
Section: A Semantic Technologies In the Iotmentioning
confidence: 99%
“…The similarity-based technique represents the method that applies situation identification decision directly after processing the current user context information. Our similarity measure extends the properties of Sim defined in Alti, Lakehal, Laborie, and Roose (2016). It is formalized as follows:…”
Section: Stage 2: Patient Situation Managementmentioning
confidence: 99%